Floating PV systems as an alternative power source: case study on three representative islands of Indonesia - Esparza, Ignacio; Olábarri Candela, Ángela; Huang, Luofeng; Yang, Yifeng; Budiono, Chayun; Riyadi, Soegeng; Hetharia, Wolter R.; Hantoro, Ridho; Setyawan, Dony; Utama, I Ketut Aria Pria; Wood, Tim; Luo, Zhenhua (MDPI, 2024)
Floating solar renewable energy is of enormous potential in Indonesia. This paper presents a comprehensive study of the design of Floating Photovoltaic (FPV) systems with Battery Energy Storage Systems (BESS) for three islands in Indonesia. These islands represent three typical scenarios in Indonesia (a) using a national grid powered by fossil fuel generators, (b) using a local grid powered by diesel generators, and (c) no grid at all. In-person surveys were conducted at these islands to collect data, and then FPV and BESS were designed to meet the demands of each island. Subsequently, the systems’ energy simulations were conducted using the System Advisor Model, demonstrating daily energy demand and supply in hour variation. Based on the results, a series of sustainability analyses were created from the aspects of economics, society, and the environment. The economic analysis demonstrated cost savings by using FPV to replace contemporary energy methods. The social analysis provides valuable insights into the local community, forming a demographic profile and obtaining perceptions and opinions regarding the new energy approach. The environmental analysis quantifies the potential CO2 emissions. Overall, the work provides valuable insights into the roadmap for implementing floating solar technologies in Indonesia which can also inform global ocean-based solar energy developments.
Keywords: renewable energy; sustainability; solar; floating photovoltaic; energy storage system; energy access